Antecedents of customer loyalty in the Malaysian hotel industry - Cheng, Boon Liat *; Lew, K. C. (International Educative Research Foundation and Publisher (IERFP) Dhaka, Bangladesh, 2015)
Creating and maintaining customer loyalty is critical for the sustainability of a hotel in a competitive environment. This research aims to examine factors that influence customer loyalty in the Malaysian hotel industry. Quantitative research approach has been adapted in this research by distributing questionnaires to 200 respondents at Kuala Lumpur International Airport (KLIA) during the survey period. Findings of this research have discovered that perceived service quality, perceived value, customer satisfaction and corporate image are the significant factors in predicting customer loyalty. Trust, on the other hand is not significant in predicting customer loyalty in the hotel industry in Malaysia. Findings of this research provide hotel operators with a better understanding on factors that could lead to customer loyalty, which subsequently will enable them to direct effective hotel services strategies to enhance their long-term business growth by building up a strong and loyal client base.